Managing Finnish-Russian Business Relationships and Networks During Conflicts - Kallio, Toni (My University, 2016)
This thesis examines management of business relationships during conflicts. The context of this study is the international political conflict which started in 2013 and is still affecting international trade relations in 2016. More specifically, this study researches the effects of the conflict in Finnish-Russian trade. The research aim is to identify the implications of a political conflict in the Finnish-Russian business relationships and networks. Furthermore, the study will explore how does a company adapt or overcome the challenges and barriers posed by the international business environment. This research combines relevant theories in management of business relationships and networks in order to review the research data through a critical research frame. The theoretical frameworks are different structures of business relationship development processes, various stages of interaction, and characteristics and functions of business relationships. Moreover, this study will examine the effect of interdependency, commitment and trust in trade relations. Also, what are the important exchange processes and how do these processes affect business relationship and overall performance of joint business operations. Qualitative single case study method was used in this research. Case company was a Finnish multinational company. To understand the changes, the data was collected and analysed through process research approach by pattern-matching and drawing temporal bracketing over two different periods of time, first period in years 2011-2013 and second period in years 2014-2016. Empirical data was collected through a semi-structured interview and additional data was collected from internal and external secondary data sources. The findings of the study confirmed the relationship between trade and conflict. However, the effects are not significant for a company in grocery retail industry which has had earlier experience in Russia and has managed its business relationships and operations effectively. Macroeconomic factors affect companies operating in foreign dynamic markets and in order to sustain changes and to adapt, companies should invest in their business relationships. Trust-based relationships and a higher level of commitment allow companies to have more efficient and beneficial outcomes before and during uncertainty. Furthermore, well-maintained and coordinated business relationships provide the ability to adapt and overcome challenges during uncertainty. Such relationships have information, financial and social exchange processes which allow the partnering firms to have successful business relationship management in dynamic market environments